Neurochemistry and Pharmacology of Addictions: An African Perspective - Mtewa, Andrew G.; Deyno, Serawit; Peter, Emmanuel L.; Amanjot, Annu; Ahovegbe, Lucrèce Y.; Sesaazi, Crispin Duncan (My University, 2019)
Neurochemistry deals with the chemistry of nervous system molecules such as neurotransmitters, autacoids, hormones and neuropeptides that direct functions of neurons. These chemicals modulate the central and peripheral nervous systems. Neurochemistry provides a platform for pharmacological and psychological understanding of addictions—their pro-genesis, prognoses, progressions and remediation’s. Neurochemistry interfaces with pharmacology, which is basically the study of uses, effects and mechanisms of drug actions